Prevalence of parasites and diseases in the African honeybee (Apis mellifera scutellata Lepeletier) : with a particular focus on Varroa destructor - Pirk, Christian Walter Werner (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.